TEMPLATE JCEC - Editorial Team/Equipe Editorial JCEC (The Journal of Engineering and Exact Sciences)
The main objective of Open-Access ISSN 2527-1075 The Journal of Engineering and Exact Sciences - JCEC is to promote and stimulate the publishing of national and international scientific research results. The journal publishes original articles, resulting from scientific research, experimental and or simulation studies in engineering sciences, technology, and similar disciplines (Electronics, Telecommunications, Bioengineering, Electrical, Computer Science, Mechanical, Chemical, Environmental, Materials, Sanitary, Civil and Industrial Engineering).